Strategi Teknologi Produksi Xilooligosakarida dari Limbah Pertanian - Febrinasari, Tantry; Irfan, Yusuf (Universitas Tangerang Raya, 2024)
The abundance of agricultural waste in Indonesia, in which the utilization is less than optimal, has encouraged a lot of research to develop technology for utilizing agricultural waste. One of the utilizations of lignocellulosic agricultural waste is as a potential raw material source for producing bioactive compounds that can be applied in functional food or nutraceutical preparations products. Xylo-oligosaccharides (XOS) are one of the oligosaccharide compounds that can be produced from the bioconversion process of lignocellulosic biomass. XOS is known to have potential as a promising prebiotic. Increasing global demand for XOS has driven various innovations in the search for efficient and environmentally friendly production methods. Therefore, developing a production strategy is very important to stimulate more sustainable XOS production. Until now, many researchers have developed different methods to obtain optimal XOS results, both in quantity and quality. This review will summarize some XOS production methodologies and strategies.